2017
DOI: 10.1016/j.ijsu.2017.01.108
|View full text |Cite
|
Sign up to set email alerts
|

Aortic and splanchnic artery aneurysms: Unusual causes of biliary obstruction – A retrospective cohort from literature

Abstract: Mechanical obstruction of the biliary tree and resultant stasis are the cornerstone of a spectrum of diseases ranging from biliary colic to fulminant cholangitis. Infrequently acquired abnormalities of the abdominal vasculature can lead to biliary obstruction. In 2010, we reported a case of acute cholangitis resulting from compression of extra hepatic bile duct by an abdominal aortic aneurysm (AAA). We subsequently conducted a follow up scoping review of literature to identify other cases of acquired abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…After extensive literature search, we came across eight substantial case reports. 916 Tin et al 17 identified 39 cases of biliary obstruction secondary to acquired aortic or splanchnic vessel abnormalities; out of these 16 were caused by AAAs, it was found that both genders are equally affected, and mean age of presentation was in seventh and eight decade.…”
Section: Discussionmentioning
confidence: 99%
“…After extensive literature search, we came across eight substantial case reports. 916 Tin et al 17 identified 39 cases of biliary obstruction secondary to acquired aortic or splanchnic vessel abnormalities; out of these 16 were caused by AAAs, it was found that both genders are equally affected, and mean age of presentation was in seventh and eight decade.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanic obstruction of the biliary tree by a pseudoaneurysm is a rarity. In 2017, Tin et al [16] conducted an extensive literature search identifying a total of 39 cases of biliary obstruction secondary to either aortic or splanchnic vessel abnormalities. Of these, 23 were caused by splanchnic arteries, most frequently by the hepatic artery, followed by the right hepatic artery and the gastroduodenal artery.…”
Section: Discussionmentioning
confidence: 99%
“…Since endovascular approaches did not exist before 1994, only studies from then on were selected in order to take the choice of treatment into consideration. 5 Only papers written in English were included. First, studies were screened by title and abstract.…”
Section: Methodsmentioning
confidence: 99%